2019
DOI: 10.1002/cncr.32115
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes by high‐risk human papillomavirus status in nonoropharyngeal head and neck squamous cell carcinomas: A propensity‐scored analysis of the National Cancer Data Base

Abstract: Background The prognostic relevance of human papillomavirus (HPV) status in patients with nonoropharyngeal (OPX) squamous cell cancer (SCC) of the head and neck is controversial. In the current study, the authors evaluated the impact of high‐risk HPV status on overall survival (OS) in patients with non‐OPX SCC using a large database approach. Methods The National Cancer Data Base was queried to identify patients diagnosed from 2004 through 2014 with SCC of the OPX, hypopharynx (HPX), larynx, and oral cavity (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 32 publications
5
53
0
Order By: Relevance
“…Chung et al 12 16,17,27 were combined with other subsites and/or were limited to patients with locally advanced disease, 28 or included patients with metastatic disease and those who did not receive appropriate therapies. 17 In comparison, our analysis of 18,19,[29][30][31] though most were limited by a small sample size…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chung et al 12 16,17,27 were combined with other subsites and/or were limited to patients with locally advanced disease, 28 or included patients with metastatic disease and those who did not receive appropriate therapies. 17 In comparison, our analysis of 18,19,[29][30][31] though most were limited by a small sample size…”
Section: Discussionmentioning
confidence: 99%
“…Proportions of HPV or p16 (a surrogate marker for HPV infection) positivity have been estimated at 13% to 24% in hypopharyngeal cancers, 9,[12][13][14] lower than those observed in nonoropharyngeal sites. Existing data regarding the prognostic value of HPV or p16 status 9,12,13,[15][16][17][18][19] in hypopharyngeal SCC is conflicting. A recent large study of US Veterans suggested that there may be a prognostic role for p16 status in nonoropharyngeal SCC, including patients with hypopharyngeal cancers, 13 although the sample size for that analysis was small.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported HPV testing rates of SCC to be as low as 10% to 11% in the NCDB for certain nonoropharyngeal head and neck subsites . Given the relatively small percentage of tumors that undergo testing, it is possible that the percentage of HPV‐positive SNSCCs could be influenced by testing biases.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported HPV testing rates of SCC to be as low as 10% to 11% in the NCDB for certain nonoropharyngeal head and neck subsites. 23 Given the relatively small percentage of tumors that undergo testing, it is possible that the percentage of HPV-positive SNSCCs could be influenced by testing biases. If, for example, certain demographic or clinicopathologic factors (eg, a young patient with no smoking history) prompted a clinician to suspect and test a tumor for HPV, the previously reported rates of HPV-positive SNSCC could be elevated artificially.…”
Section: Methodsmentioning
confidence: 99%
“…Sexual behaviors such as oral sex practice and having multiple lifetime number of oral or genital sexual partners were associated with these cases (Emmett et al, 2018;Laprise et al, 2019). Regarding the prognosis, a significantly better survival and treatment response were observed among those with HPV infection (Li et al, 2018;Tian et al, 2019).…”
Section: Human Papillomavirus 16 and 18 Infection In Oral Cancer In Tmentioning
confidence: 96%